2022
DOI: 10.1186/s12913-022-07661-8
|View full text |Cite
|
Sign up to set email alerts
|

Using Andersen’s model of health care utilization to assess factors associated with COVID-19 testing among adults in nine low-and middle-income countries: an online survey

Abstract: Background This study aimed to investigate, using Andersen’s model of health care utilization, factors associated with COVID-19 testing among adults in nine low- and middle- income countries. Methods In between 10 December 2020 and 9 February 2021, an online survey was organized in nine low- and middle-income countries. In total 10,183 adults (median age 45 years, interquartile range 33–57 years, range 18–93 years), including 6470 from Brazil, 1738… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Although our study shows that testing uptake can be increased by facilitating access to testing, there are many other factors that influence testing motivation and testing uptake [ 30 , 31 ]. Studies in several other countries showed associations between educational level or ethnicity and low testing uptake [ 16 , 32 ]. Others found factors such as perceived discrimination at work, concerns of individual’s privacy, and feelings towards testing to influence test intentions [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although our study shows that testing uptake can be increased by facilitating access to testing, there are many other factors that influence testing motivation and testing uptake [ 30 , 31 ]. Studies in several other countries showed associations between educational level or ethnicity and low testing uptake [ 16 , 32 ]. Others found factors such as perceived discrimination at work, concerns of individual’s privacy, and feelings towards testing to influence test intentions [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the individual level, lower economic status is associated with worse outcome when infected with COVID-19 [ 27 , 29 ]. We used unemployment levels to which tend to be high in African countries as a measure of poverty levels for the country.…”
Section: Methodsmentioning
confidence: 99%
“…The Andersen’s conceptual model, however, has some context-specific challenges Law et al 23 argue the model may not give enough attention to cultural dimensions and social interactions but it is still a widely used conceptual framework for most studies on HSU 24–26. The Andersen’s conceptual model over the years has undergone modifications to include those for vulnerable populations,27 which may be relevant for sub-Saharan Africa.…”
Section: Introductionmentioning
confidence: 99%